Penanggulangan Terhadap Tindak Pidana Pertambangan Mineral Dan Batubara di Wilayah Hukum Kepolisian Daerah Gorontalo - Adawiyah Pakaya; Moh. Rusdiyanto U. Puluhulawa; Nuvazria Achir (Lembaga Pengembangan Kinerja Dosen, 2024)
Community Service Activities to examine countermeasures against mineral and coal mining crimes in the jurisdiction of the Gorontalo Regional Police and the Inhibiting Factors. The activity method is field study, the research method used in the research is empirical with qualitative descriptive data analysis which describes and describes field data and facts. Based on the results of the research, the handling of mineral and coal mining crimes in the jurisdiction of the Gorontalo Regional Police is carried out by carrying out repressive efforts. This activity includes a series of actions aimed at uncovering cases that have occurred, where the stages start with a series of inquiries, inquiries and other coercive measures authorized according to the law. Carrying out preventive efforts, including a series of activities aimed at preventing crimes before they occur, where investigators make arrangements for security, including conducting patrols at locations thought to contain indications of criminal acts. In relation to criminal acts, especially mining, the Gorontalo Regional Police provides guidance and encouragement to the community to actively participate in efforts to prevent and ward off crime, by reporting suspicious incidents; and Carrying out pre-emptive efforts, starting from conducting an analysis of regional conditions and potential vulnerabilities, collaborating with related elements, to anticipate violations or crimes. The inhibiting factors in dealing with mineral and coal mining crimes in the Gorontalo Regional Police are: Legal Content Factor, where the imposition of sanctions does not include the threat of a minimum sentence, thus affecting the police, public prosecutors and judges' decisions to be less strong; Law Enforcement Factor, where officials can be a supporting factor in the implementation of the law, or actually become a protector for the perpetrator; Community Cultural Factors relate to the basic values ​​of what is good and what is bad, in order to support the implementation of law, which originates from the community's legal understanding and attitudes or behavior. Facilities and facilities factors, where the police have constraints in terms of the number of competent human resources, thereby maximizing the role of PPNS investigators from other agencies.